PERKEMBANGAN EKOWISATA DI BALI : “UPAYA PELESTARIAN ALAM DAN BUDAYA SERTA PEMBERDAYAAN MASYARAKAT LOKAL” - Putu Emy Suryanti; Kadek Bayu Indrayasa (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
Bali is one of the tourist destinations for tourists to Indonesia. Bali has tourism assets in the form of unspoiled natural beauty, unique cultural heritage, and the friendliness of the local community. The existence of tourist objects and attractions in Bali is expected to bring benefits, especially for the surrounding community in generating new jobs. With the new employment opportunities, it is hoped that the welfare of the community will increase. However, it turns out that not only are the positive impacts obtained by the existence of tourist objects and attractions, but also many negative impacts. The emergence of negative impacts from tourism activities, encourages a change in the tourism paradigm, namely mass tourism to new tourism that tends to be environmentally friendly, one of which is ecotourism. Ecotourism is expected to be able to become tourism that is responsible for the preservation of nature and contribute to improving the welfare of local communities. With the development of the ecotourism concept in Bali, it is hoped that it will be able to preserve the nature and local culture of Bali as well as increase the welfare of the local community through community empowerment.